Pathological changes of the vertebrae in Asian female elephant from Zagreb Zoo - Mihelić, Damir (Array, 2008)
Vertebrae of a 65 year old Asian female elephant that died in Zagreb Zoo were studied. Significant spondylosis-like changes, as well as osteophytes, were observed. Despite age significant osteoporotic changes were not observed.